O036/#221 Intrathoracic surgery as part of primary cytoreduction for advanced ovarian cancer – going to the next level: a memorial sloan kettering team ovary study. (4th December 2022) - Kahn, Ryan; Mcminn, Erin; Boerner, Thomas; Roche, Kara Long; Zivanovic, Oliver; Gardner, Ginger; Sonoda, Yukio; O'Cearbhaill, Roisin; Grisham, Rachel; Huang, James; Park, Bernard; Abu-Rustum, Nadeem; et al.
Abstract : Objectives: We report on a cohort of patients undergoing intrathoracic cytoreduction as part of primary debulking surgery (PDS), assessing safety and survival outcomes. Methods: We conducted a single center, database review of patients with stage IIIB-IV ovarian carcinoma who underwent intrathoracic cytoreduction as part of PDS at our institution between 01/2001–12/2019. Patients were excluded if they received neoadjuvant chemotherapy. Results: During the study, 179 patients had intrathoracic surgery as part of PDS. This represents 11% (179/1579) of patients who had a PDS at our institution during this time. Supradiaphragmatic/cardiophrenic lymph nodes were excised in 64% of patients (114/179); mediastinal (not cardiophrenic) nodes 13% (23/179); pleural nodules 7% (12/179); lung parenchyma 1% (2/179), and multiple intrathoracic areas 16% (28/179). Complete gross resection (CGR) was achieved in 73% of patients (127/179), 26% (44/179) had optimal cytoreduction (1–10 mm of residual disease (RD)), and 1% (2/179) underwent suboptimal cytoreduction (>10 mm of RD). Median length of follow-up among survivors was 55 months. Patients with an intrathoracic cytoreduction of carcinoma where CGR was achieved had a median OS of 97 months versus 54 months following an optimal cytoreduction with RD (p = 0.0036). Patients with an intrathoracic cytoreduction where CGR was achieved had a median PFS of 22.1 months versus 14.4 months following an optimal cytoreduction with RD (p = 0.04). Conclusions: Intrathoracic cytoreduction during PDS for advanced ovarian cancer is safe and feasible. CGR can be obtained in patients with intrathoracic disease if properly selected. Resection of all gross RD including intrathoracic disease significantly improves both PFS and OS.